Inflammatory response of skin autografting in the chicken - SHRIVASTAVA, A B; VEGAD, J L; KATIYAR, A K (The Indian Journal of Animal Sciences, 2013)
Pathology of skin autografting in the chicken showed grossly cyanosis and oedema in the beginning. Histopathologically,endothelial swelling and vascular wall degeneration. endothelia swelling and spongiosis, and focal degeneration. wereobserved. These changes were gradually reduced and the graft appeared healthier at seventh day. The vascular and cellularchanges conformed with the pattern of reaction in the chicken in response to incised wounding. Noteworthy finding was theformation of prominent perivascular lymphoid aggregates.